Palestinian refugees in Lebanon : from co-ethnics to a racialized minority - Serhan, Waleed (Trinity College (Dublin, Ireland). Department of Sociology, 2015)
This study employs critical race theory to understand, explain, and theorize the exclusion and racialization of Palestinian refugees in Lebanon. There exists vast and diverse literature on the exclusion of Palestinians in Lebanon, however, this study is the first to examine the exclusion of Palestinians by the Lebanese state through the theoretical lens of racialization. As such, it does not only enhance our understanding of Palestinian exclusion but also contributes to sociological knowledge in temis of assessing the usefulness of critical race theory in the Lebanese-Palestinian context. The importance of this particular context lies in that Lebanon is a consociational state founded on power-sharing between confessional communities officially recognized by the state, while Palestinian outsiders fail to fit these official administrative categories of consociation.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin